The DNA repair kinase ATM regulates CD13 expression and cell migration - Stevenson, Louise K.; Page, Amy J.; Dowson, Matthew; ElBadry, Sameh K.; Barnieh, Francis M.; Falconer, Robert A.; El-Khamisy, Sherif F. (Frontiers in Cell and Developmental Biology, 2024)
Classically, ATM is known for its role in sensing double-strand DNA breaks, and subsequently 13 signaling for their repair. Non-canonical roles of ATM include transcriptional silencing, ferroptosis, 14 autophagy and angiogenesis. Angiogenesis mediated by ATM signaling has been shown to be 15 VEGF-independent via p38 signaling. Independently, p38 signaling has been shown to upregulate 16 metalloproteinase expression, including MMP-2 and MMP-9, though it is unclear if this is linked to 17 ATM. 18Here, we demonstrate ATM regulates aminopeptidase-N (CD13/APN/ANPEP) at the protein level. 19Positive correlation was seen between ATM activity and CD13 protein expression using both 20 'wildtype' and knockout (KO) ataxia telangiectasia cells through western blotting; with the same 21 effect shown when treating neuroblastoma cancer cell line SH-SY5Y, as well as AT-WT cells, with 22 ATM inhibitor (ATMi; KU55933). However, qPCR along with publically available RNAseq data 23 from Hi et al, 2021, demonstrated no change in mRNA levels of CD13, suggesting that ATM 24 regulates CD13 levels via controlling protein degradation. This is further supported by the 25 observation that incubation with proteasome inhibitors lead to restoration of CD13 protein levels in 26 cells treated with ATMi. Migration assays showed ATM and CD13 inhibition impairs migration, 27 with no additional effect observed when combined. This suggests an epistatic effect, and that both 28 proteins may be acting in the same signaling pathway that influences cell migration. 29This work indicates a novel functional interaction between ATM and CD13, suggesting ATM may 30 negatively regulate the degradation of CD13, and subsequently cell migration. 31